Economic Indicators for Analyzing the Spatio-Temporal Characteristics of the Supply and Demand for Ecosystem Services - Kosenok, Yury; Gorbanyov, Vladimir; Makar, Svetlana; Bubnov, Vladimir (Journal of Environmental Accounting and Management, 2026)
The purpose of this study is to improve the process of evaluating ecosystem services at the local, national, and international level. The following approaches were used in the study: computational, classification, and cartographic methods, aerospace, geoinformation technologies. The research uses a five-level framework for defining ``final ecosystem services''. Such framework can be applied on specific territories if transformed according to the following scheme: type of a class-class-group-division-section. This scheme allows one to specify the indicators of an ecosystem service and clarify its functions at each hierarchical level. To improve objectivity of area's ecological integrity evaluation, as well as accuracy and completeness of input materials for further evaluation of ecosystem services, it is proposed to determine the degree of ecological stability, the level of environmental risk and the degree of anthropogenic impact as basic indicators of the studied region. The approach is applied for the territory of an average village council. The implementation of a ``donor-recipient'' system of interregional relations is proposed for two ecosystem services: prevention of water erosion and recreation. Using cartographic materials and historical archival aerospace images for desktop and field research on the assessment of ecosystem services reduces the time used for this work. Developing and implementing land consolidation projects somewhat neutralize the negative effects of fragmentation and the existing inconsistency of administrative boundaries and ecosystems.